Tourism in Ibiza Island and its destination life cycle. - Krendzelak, Justyna (2008)
The following research will look at tourism offer on Balearic Island, Ibiza as well as attractiveness of particular holiday packages in regards to destination life cycle. Today’s competitiveness on holiday market requires certain originality from particular destination. Additionally in order to create high demand, offers on particular market should be affordable as well as meet customers needs and preferences. Therefore profile of current holiday options for tourist on Ibiza will be provided.